Tautiniai stereotipai klasikinėje ir romėniškojoje Graikijoje: Herodotas ir Diodoras apie graikus ir kitus - Juchnevičienė, Nijolė (Literatūra, 2015)
Though Diodorus, who lived in politically and economically decayed Greece, dominated by Romans, is separated from Herodotus, the historian of independent and victorious Greece, by the interval of four centuries, the conception of Greekness as reflected in Herodotus’ History is a fulcrum to perceive the selfawareness of Greeks in the I century B.C. nevertheless. It is obvious that Diodorus knew Herodotus’History well. Herodotus, living in times, that were deeply affected by the ta Mēdica, was compelled to think over the idea of national identity and the relation of traditional Greek values to the culture, or cultures, of dominant political power. His approach to explain political history is to perceive the culture of nations, involved in the political process. This way to understand history was not invented by Herodotus, but was inherited and handed down by him to the subsequent historians, yet Herodotus can be put before the others because of his capability to see self in the other; self and other form an indissoluble unity in his History. Other cultures are described in analogy and / or contrast with Greek culture, and Greek is not always the best. Barbarian in his text indicates belonging to a different, but by no means to the inferior civilization. Barbaroi are usually referred to as cultural predecessors of Greece, which is often presented only as a successor of very old barbarian traditions. Opposition inside the Greek culture is sometimes stressed by Herodotus more emphatically than opposition between Greeks and the others. In my opinion, he tries to show that the idea of panhellenism, upon which the Athenian ideology was based in Herodotus’ times, is a political fiction, that was not and could not be true to life. Diodorus sticks to comparative methods describing the history of human civilization, but his objectivity is imaginary: it is rather a matter of the traditional ethics of scientific discourse for him. He is deeply convinced that barbarians are inferior compared to Greeks and Greece is the moral and intellectual leader of the oikoumenē. The glorious history of Greece and the preservation of its traditional values is not only an intrinsic, but universal cultural factor as well. This is his historiosophic idea, which can be applied to explain his attitude to Rome. Romans are not ascribed to barbarians by him, but at the same time they are not Greeks. Rome belongs to the third cultural category. Roman history is a history of an advance of the expansive political power, which can be compared to the history of the Persian empire at the end of the VI century B.C. Therefore Diodorus pays so much attention to the Thermopylean episode in his History. This episode is symbolic in Diodorus’ History, signifying to his contemporaries the opportunities that are lost, but ought to have been taken, and the decline of the aretē, which once undamaged would have saved Greece.